Outdoor Advertising as Visual Communication: The Example of Ankara - Çiftçi, Dilan; Karabulutlu, Büşra Betül (Journal of History Culture and Art Research, 2020)
In today's world, where advertisements and advertising have become extremely important and all aspects of outdoor advertising have all become crucial. Striking examples of outdoor advertising from around the world, the contribution of advancing technology, especially the augmented reality concept that has been frequently investigated recently to the advertising sector and the contribution of advertising to the brand are examined in this study. The main aim of the study is to present outdoor advertising in Turkey and in the world from different perspectives and to illustrate what is advertising, how it should be done, what should be paid attention to, what are the effects on human psychology and perception. In this way, the open-air advertisements in Ankara's most crowded squares (n = 4) were examined in November 2019 for a period of 1 (one) month. In this study, one of the qualitative research methods, document analysis technique was used. In this context, the analysis of the sample of the study was analyzed in terms of the structure, feature, type and similar elements of the media with the support of the literature.